Alcman's Muses: Alcman PMGF 28 (85 Calame), The ΦΙ-Case and the Syntax of Divine Invocation in Greek and Indo-European. (13th December 2016) - Barnes, Timothy G.
Abstract: In this article a new interpretation of the problematic form (Alcman PMGF 28 (85 Calame)) is proposed on the basis of a both a fresh examination of the history and prehistory of the ϕι-case and an overview of the syntax of coordinated pairs in various Indo-European languages.